(untitled) (Bangladesh Critical Care Journal, 2014)
Patients with congenital adrenal hyperplasia (CAH) usually presents with varied manifestations. In female, it can manifest as ambiguous genitalia, salt wasting crisis or androgen excess in puberty depending on the severity of enzyme deficiency. Here, we report a four and half year old girl who developed salt wasting crisis in the neonatal period. Prompt diagnosis and immediate glucocorticoid and fludrocortisone replacement saved her life. High index of suspicion is needed to diagnose CAH and continued replacement of glucocorticoid and mineralocorticoid is needed to suppress virilization of the female child and prevent further crises. Bangladesh Crit Care J March 2014; 2 (1): 38-39